ANALYSIS OF VARIATION HYGROTHERMAL ARISING BY INFLUENCE OF OCCUPATION OF LAND IN THE CITY CUIABÁ-MT - Santos, Flávia Maria de Moura; Musis, Carlo Ralph de; Nogueira, José de Souza; Pinto Júnior, Osvaldo Borges; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707699 The factors that are processed on the urban boundary layer eventually creating a climateof its own in urban areas that related to types and degrees of density and land use have the abilityto change the climate elements that make up the local atmosphere. Therefore, this study aimed to identify differences hygrothermal intraurbana Cuiaba-MT, Brazil, for mobile transects night in fourseasons using digital hygrometer, protected shelter, attached to the side of a vehicle that left theperiphery (rural), arriving at the opposite end of town, in the directions East-West and North-South. It is noteworthy that areas under the influence of masses of vegetation, microclimateshowed different to other areas of the city because there is a contribution to the energy loss tothe environment and consequent decrease in values of air temperature and increased relativehumidity, showing the importance of implementing parks in places like harsh climate in Cuiaba.